Hybrid photomagnetic modulation of magnetite/gold-nanoparticle-deposited dextran-covered carbon nanotubes for hyperthermia applications. (22nd August 2018) - Sadaphal, Varun; Mukherjee, Siddhartha; Ghosh, Santaneel
Abstract: The hybrid photomagnetic (PMA) stimulation effect, which was found to be significantly stronger than stand-alone magnetic and photothermal responses, was characterized on magnetite/gold-nanoparticle-deposited dextran-covered carbon nanotube structures (DIGCNTs). The designed nanostructures demonstrated excellent biocompatibility on a neural cell model; however, the viability of tumor suppressor p53-deficient NE-4C cells was severely affected when activated by low-intensity PMA stimulation (50 Oe, 155 kHz; 400 mW/cm 2, 530 nm laser) at a concentration as low as 50 µg/mL. The acute toxicity of this unique hybrid actuation-hybrid material combination, coupled with excellent innate biocompatibility, may be extremely relevant in the development of in vivo hyperthermia.